USULAN PERBAIKAN PENATAAN PENYIMPANAN POLA PADA RUANG RND (RESEARCH AND DEVELOPMENT) DI PT. CARTENZ INDONESIA DI KARANGANYAR, JAWA TENGAH - Tina Puspitasari1; Rofiatun Nafiah (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2018)
PT Cartenz Indonesia is a company that produces outdoor equipment, one of which is an outdoor bag. The process of making bags begins with making patterns, which will be used as a reference in making bag samples. In addition to pattern making, pattern storage can affect the length of the sample making process. Problems encountered at PT. Cartenz Indonesia in the form of an inefficient pattern storage arrangement. The purpose of this research is to identify problems and provide solutions for storing patterns in the research and development room. Data collection methods used were direct observation and documentation. The data were then analyzed and the problems solved by designing the pattern storage. The results of the research shows that there is time reduction until 21 minutes for finding the pattern